Features Of Civil Law Regulation Of Insurance Investment Activities (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article, based on an analysis of civil legislation governing relations in the field of investment insurance, describes the features of civil regulation of investment insurance. The role of the state in the process of legal regulation of investment activities in the Republic of Uzbekistan, attention is paid to the peculiarities of the legal status of foreign investments. The article provides definitions of basic concepts in the field of insurance of investment activities. A comparative analysis of the civil legislation of the Republic of Uzbekistan in force in the field of regulation of insurance of foreign investments and the investment legislation of the Russian Federation was carried out. Also, the views of legal scholars on the problems of legal regulation in the field of investment activity are presented.